2018
DOI: 10.1093/scan/nsy055
|View full text |Cite
|
Sign up to set email alerts
|

Feeling left out: depressed adolescents may atypically recruit emotional salience and regulation networks during social exclusion

Abstract: Depression is associated with negative attention and attribution biases and maladaptive emotion responsivity and regulation, which adversely impact self-evaluations and interpersonal relationships. Using functional magnetic resonance imaging, we investigated the neural substrates of these impairments. We compared neural activity recruited by 126 clinically depressed and healthy adolescents (ages 11–17 years) during social exclusion (Exclusion > Inclusion) using Cyberball. Results revealed significant interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 117 publications
5
25
0
1
Order By: Relevance
“…However, the current research suggests that if youth have an alternative nurturing social environment (e.g., a supportive family), they may be able to overcome the maladaptive outcomes often associated with this neural sensitivity and even transform it into a protective factor. This idea is supported by research showing that certain regions implicated in social‐affective processing (including the dACC, sgACC, and insula) are responsive to bivalenced (i.e., both negative and positive) social feedback (Jankowski et al., ; Schriber & Guyer, ), and that heightened activation in these regions can predict both healthy and unhealthy developmental outcomes (for a review, see Schriber & Guyer, ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the current research suggests that if youth have an alternative nurturing social environment (e.g., a supportive family), they may be able to overcome the maladaptive outcomes often associated with this neural sensitivity and even transform it into a protective factor. This idea is supported by research showing that certain regions implicated in social‐affective processing (including the dACC, sgACC, and insula) are responsive to bivalenced (i.e., both negative and positive) social feedback (Jankowski et al., ; Schriber & Guyer, ), and that heightened activation in these regions can predict both healthy and unhealthy developmental outcomes (for a review, see Schriber & Guyer, ).…”
Section: Discussionmentioning
confidence: 93%
“…Rather than selecting regions that robustly activate during Cyberball, and that may therefore not show individual differences, our aim was to focus on regions that may differentiate sensitive and insensitive individuals. For instance, these regions consistently show activation during Cyberball that correlates with individual differences such as time spent with peers (Masten, Telzer, Fuligni, Lieberman, & Eisenberger, ), chronic peer rejection (Will, van Lier, Crone, & Güroğlu, ), and depression (Jankowski et al., ; Masten et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it is found that while depressed individuals show decreased striatal response to monetary reward (Forbes et al ., 2006), they exhibit increased amygdala response to social reward (social acceptance; Davey et al ., 2011). Furthermore, depressed individuals have greater activation for social punishment in brain areas including the ventral lateral pre-frontal cortex (VLPFC), insula and subgenual anterior cingulate cortex (sgACC), all regions of the ‘social pain’ network (Silk et al ., 2014; Rudolph et al ., 2016; Kumar et al ., 2017; Jankowski et al ., 2018). In contrast, reduced reactivity across multiple brain regions including pre-frontal regions, parietal cortex, amygdala and putamen have been observed for monetary losses in individuals with depression (Knutson et al ., 2008; Schiller et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also have explored the neural processes of specific social interactions or emotions, such as interpretation of ambiguous social cues (Davis, Neta, Kim, Moran, & Whalen, 2016), sense of fairness and justice (Klapwijk et al, 2016), guilt and shame (Whittle, Liu, Bastin, Harrison, & Davey, 2016), hostility (Nakagawa et al, 2017), and retaliation (Emmerling et al, 2016), and how cerebral responses to social interaction vary with individual traits in approach and inhibition (Radke et al, 2016). Other work elucidated the neural processes of depression in relation to social threat processing (Jankowski et al, 2018) and the effects of mindfulness on the management of social rejection (Martelli, Chester, Warren Brown, Eisenberger, & Nathan DeWall, 2018). These findings provide important clues to the biological underpinnings of various dimensions of social interaction.…”
Section: Introductionmentioning
confidence: 99%